Rancangan Acak Kelompok (RAK) pada Analisis Pengaruh Jenis Kontur dan Kedalaman Tanah terhadap Karakteristik Tanah - Kasih Simbolon; Christine Simatupang; Diah Ayu Lestari; Rotua Evelyn Tesalonika Sinambela; Sudianto Manullang; Putri Maulidina Fadilah (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the influence of soil contour types and depths on soil characteristics using a Randomized Block Design (RBD) method. The research data were obtained from a secondary dataset encompassing physical and chemical soil characteristics across three contour types (Top, Slope, and Depression) and four depth levels (0-10 cm, 10-30 cm, 30-60 cm, and 60-90 cm). The analysis results indicate that soil contour types and depths do not significantly affect most soil characteristics, such as pH, nitrogen content, phosphorus, calcium, sodium, and soil conductivity. However, significant effects were observed on magnesium (Mg) and potassium (K) content. Conversely, area grouping showed significant effects on nearly all tested soil characteristics. These findings highlight the importance of considering geographical variations in soil management to enhance the efficiency and sustainability of agricultural practices. Further research is recommended to explore other factors affecting soil characteristics, such as climate and vegetation types, to support more optimal land management strategies.